Sistem Informasi Geografis Pemetaan Data Sebaran Penyakit Demam Berdarah Di Wilayah Kerja Puskesmas Karya Maju - Maulana, Muhammad Mico; Sanmorino, Ahmad; Marcellina, Dona (Jurnal Ilmiah Informatika Global, 2025)
Dengue Hemorrhagic Fever (DHF) remains a serious public health problem in Indonesia. In rural areas with limited infrastructure, conventional disease monitoring methods hinder effective dengue prevention. This study aims to design and implement a Web-Based Geographic Information System (GIS) to map the distribution of DHF cases in the working area of Puskesmas Karya Maju. The system is developed using the Agile method through stages of observation, system design, implementation, and testing. The application is built using Laravel, MySQL, and Leaflet.js and includes features such as interactive maps, patient and village data, and real-time statistical visualization. Black Box Testing ensures that all features function correctly. The results show that the system helps improve dengue surveillance and facilitates better decision-making for prevention.